HAMBATAN – HAMBATAN BELAJAR SISWA KELAS X PADA KOMPETENSI MEMBUAT POLA ( PATTERN MAKING ) TEKNIK KONTRUKSI JURUSAN TATA BUSANA DI SMK NEGERI 8 PADANG - Devita, Nova; Zahri, Wildati; Yasnidawati, Yasnidawati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This research begin from the phenomena in SMK 8 Padang that some students are not good in making pattern. It is shown by the obstacles in making the measurement, making the basic pattern and breaking pattern. The aim ofÂ this research is to see how are the obstacles that faced by the students in making the measurement, making the basic pattern and breaking the pattern in pattern making competences by using construction technique in SMK 8 Padang. The kind of this research is quantitative descriptive that describe, explain and interpret as the reality. The population is 22 students, which are all students in X grade fashion department. Data collection is using questionnaire with 27 items. Data analysis using percentage technique and respondents total achievement. The result shows that the students obstacles in pattern making competence in SMP 8 Padang is still high. 45% students experienced obstacle in making measurement with middle category, 36% students experienced obstacle in making basic pattern in low category and 41% students experienced obstacle in breaking pattern in low category. It means that the students experienced obstacle in pattern making competence by using construction technique in SMK 8 Padang. Â Kata kunci: Hambatan Belajar Siswa